MASYARAKAT ISLAM INDONESIA PADA ABAD MODERN DAN KONTEMPORER - Saiul Anah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2021)
The expression of the Indonesian Islamic Community is the response ofMuslims to the development of modernity, so that the big of the Islamic revival isdivided into three groups, namely Islamic revivalisme, Islamic reformisme and Islamicfundamentalisme. Revival Islam gave to several movement groups, including:patienting Islam, traditionalist Islam, orthodox Islam, Neo-revivalisme, andconservative Islam. While reformist Islam gave to several movements, such as:modernist Islam, liberal Islam, substantial Islam, and Neo-modernists. while,fundamentalist Islam gave to radical Islam, militant Islam and even terrorisme.Methodologically the understanding of Islam, the modern and contemporary Islamicthought movements, as stated by loualy sufi consists of two, namely groups that use andapply the classical Islamic system and groups that use the paradigm of modern Westernepistemology in total or with a process of integration between modern scholarship. Westwith the treasures of Islamic scholarship. Based on this, it is worth mentioning that thediversity of Indonesian Muslims as a national treasure must be knitted so that interreligiousharmony is created as a characteristic of the true character of the Indonesiannation.